Bone Morphogenetic Protein 7 Is Expressed in Prostate Cancer Metastases and Its Effects on Prostate Tumor Cells Depend on Cell Phenotype and the Tumor Microenvironment - Colm Morrissey; Lisha G. Brown; Tiffany E.M. Pitts; Robert L. Vessella; Eva Corey (Neoplasia: An International Journal for Oncology Research, 2010)
Bone morphogenetic protein (BMP) signaling is important in prostate development and prostate cancer (PCa) progression. However, because of the multiple effects of different BMPs, no final conclusions have been made as to the role of BMPs in PCa. In our studies, we have focused on BMP-7 because it is involved in prostate morphogenesis, and its expression is regulated by androgens. The objective of our study was to determine BMP-7 expression in PCa metastases and investigate the effects of BMP-7 on PCa cells. Our results show that BMP-7 is expressed in metastatic PCa and its levels are increased in castration-resistant PCa versus androgen-dependent PCa, whereas the expression of BMP-7 is decreased in primary PCa versus normal prostate. Our in vitro results show that BMP-7 inhibits proliferation of androgen-sensitive LNCaP cells, stimulates androgen receptor signaling, increases the expression of differentiation-associated genes, and decreases the levels of some wingless-regulated transcripts. Interestingly, these effects were not detected in C4-2 castration-resistant PCa cells. In vivo expression of BMP-7 in castration-resistant C4-2 cells did not alter proliferation when these cells were grown subcutaneously, but their growth was inhibited in the bone environment. In summary, our results show that BMP-7 is expressed at the highest level in advanced castration-resistant PCa cells and that the inhibitory effects of BMP-7 are dependent on the differentiation status of PCa cells and the tumor microenvironment. Further studies are needed to identify changes in BMP-7 signaling that lead to the loss of its control of proliferation during PCa progression.